Comparison of Continuous Nerve Block Versus Patient-Controlled Analgesia for Postoperative Pain and Outcome After Talar and Calcaneal Fractures. (November 2014) - Luiten, Willem E.; Schepers, Tim; Luitse, Jan S.; Goslings, J. Carel; Hermanides, Jeroen; Stevens, Markus F.; Hollmann, Markus W.; van Samkar, Gan
Background: Talar and calcaneal fractures and their treatment can cause severe postoperative pain. We hypothesized that a continuous peripheral nerve block (CPNB) would reduce pain scores more effectively than systemic analgesics, improve recovery, and lead to reduced length of stay (LOS). Methods: Over a 3-year period patients undergoing open reduction and internal fixation (ORIF) of a talar or calcaneal fracture were retrospectively analyzed. Patients received a CPNB catheter preoperatively or intravenous patient-controlled analgesia (PCA) postoperatively. Primary endpoint was Numerical Rating Scale (NRS) scores on postoperative day 1. Secondary endpoints were NRS scores up to day 3, opioid requirement, analgesia-related side effects, intraoperative blood loss, infection, and LOS. Eighty-seven patients were analyzed; 70 with calcaneal fracture, 21 with talar fracture, 4 with both. In all, 40 patients received CPNB, 47 patients PCA. Results: Median NRS scores on day 1 were 1.0 (IQR 3) in the CPNB group and 2.0 (IQR 3) in the PCA group ( ns ). Median LOS for patients with CPNB was 5 days (IQR3) and PCA 4 days (IQR 2 ns ). Blood loss and incidence of local infections were comparable in both groups. Opioid requirement was significantly increased in the PCA group ( P < .01). Conclusion: Significant advantages or disadvantages were not seen in either group. However, the PCA group required about 30-fold more opioids compared to the CPNB group on day 1, although that did not lead to an increased number of side effects. Level of Evidence: Level III, retrospective comparative series.